1976
DOI: 10.1037/0022-006x.44.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of masculine and feminine sex role identities as independent dimensions.

Abstract: Recent trends in conceptualizing sex role behavior have emphasized the independent development of masculinity and femininity. This has required a logical extension of sex role outcomes from the bipolar alternatives of being masculine or feminine to a quadripolar typology in which sex roles could develop as masculine and feminine, masculine and not feminine, feminine and not masculine, or neither masculine nor feminine. Investigation of this extended typology requires a masculinity-femininity scaling technique … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
114
2
3

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 247 publications
(124 citation statements)
references
References 21 publications
2
114
2
3
Order By: Relevance
“…We conducted a pilot study (N = 254) to assess the stimulus materials on a 10-item measure (α = 0.82) based off previously established dimensions of masculinity and femininity [e.g., 1,18]. Fifty percent of participants were male with the average age of 23.23 (SD = 4.68).…”
Section: Resultsmentioning
confidence: 99%
“…We conducted a pilot study (N = 254) to assess the stimulus materials on a 10-item measure (α = 0.82) based off previously established dimensions of masculinity and femininity [e.g., 1,18]. Fifty percent of participants were male with the average age of 23.23 (SD = 4.68).…”
Section: Resultsmentioning
confidence: 99%
“…In a first step, we reviewed studies that assess the fundamental dimensions by means of trait words (Abele & Wojciszke, 2007;Anderson, 1968;Bem, 1974;Cuddy, et al, 2007;Diehl, Owen, & Youngblade, 2004;Fiske, et al, 2002;Heilbrun, 1976;Judd, et al, 2005;Meadows, 2005;Spence, Helmreich, & Stapp, 1974;Tausch, Kenworthy, & Hewstone, 2007;Wentura, Rothermund, & Bak, 2000;Wiggins, 1979;Wojciszke, 2005) and created an item-pool of 304 adjectives. In a second step, we reduced this pool to a list of 69 trait words.…”
Section: Pretest: Selection Of Trait Wordsmentioning
confidence: 99%
“…These differentiated responses can be observed in gender studies (Bem, 1974(Bem, , 1975(Bem, , 1977Heilbrun, 1976;Lorr & Maning, 1978;Silvern & Ryan, 1979), more specifically in studies that deal with psychological androgyny, as well as the studies by Helgeson (1994), in which she reported that individuals who possessed agentic and communal traits presented lower disease incidences than other individuals.…”
mentioning
confidence: 90%
“…A parallel can be made of the effect of schema development with studies by Moscovici (1961), in which the author demonstrated that the degree to which knowledge of a given object increases, the objectification of the same diminishes. Behavioral flexibility and the freedom to judge certain situations using parameters distinct from those circumscribed by the schemas were amply observed in a number of studies involving psychological androgyny (Bem, 1974(Bem, , 1975(Bem, , 1977Heilbrun, 1976;Heilbrun & Pitman, 1979;Helmreich, Spence, & Holahan, 1979;Kalin, 1979;Spence et al, 1975).…”
Section: The Synthesis Variablementioning
confidence: 99%